(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study is an attempt to comparative analyzes the food consumption pattern in Urban and Rural Maharashtra. An inquiry has been made to find whether there is any change in the consumption of food and non-food items among different Income groups. Differences in the category, quantity, mode of purchase, place, and frequency of purchase are also analyzed. The changes that have taken place during 2013-2023 are highlighted. The study also analyses the nature of the rural-urban divide with regard to the consumption pattern of households.